A Critique on the Book "Socioeconomic Situation of Malaali at the Beginning of Islam" Sayyed Mohammad Reza Hosseini - Sayyed Mohammad Reza Hosseini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the books published on the history of the early Islamic era is by Jamal Jawdah "Socioeconomic Situation of Malaali at the Beginning of Islam". This book deals with the critical ear of early Islam and treats the clash of the Omavids with the Malaali. This book has a number of shortcomings, such as lack of innovation, lack of organization, having no definite conclusion, lack of proper sources, disregarding modern methods of research, etc. These drawbacks have embattled the writer, and he has not been successful in explaining the socio-economic conditions of Malaali in early Islam. The mentioned book has logical-critical and library-based methods and was criticized in an unbiased way. Some parts have been reviewed briefly.